(untitled) (Bangladesh Journal of Otorhinolaryngology, 2011)
Exogenous foreign bodies in tracheo bronchial tree are not uncommon, particularly in children. The gold standard principal of foreign body management is bronchoscopic removal and this procedure becomes difficult and challenging in cases of large and smooth foreign body as occur in our case. The present article reports a case of unique and large foreign body i.e. intact glass bulb in right main bronchus. Key words: Foreign body; Bronchus. DOI: http://dx.doi.org/10.3329/bjo.v17i2.8854 BJO 2011; 17(2): 132-134